2017
DOI: 10.1149/2.0101705jes
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies of Cortisol-Imprinted Prepolymerization Mixtures: Structural Insights into Improving the Selectivity of Affinity Sensors

Abstract: The binding affinity of molecularly imprinted polymers (MIPs) relies on the mechanisms and the extent of the functional monomertemplate interactions present in the prepolymerization mixture. Thus, a clear understanding and optimizing the physiochemical parameters governing these interactions is key in designing and modeling MIPs with good selectivity. Quantum chemical method was applied here for the theoretical investigation into the interaction between cortisol and pyrrole in a molecularly imprinted prepolyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The mainstay of this framework is a surrogate model, upon which tailored data analytics methods can be further employed to quantify the relationship between synthesis parameters of e-MIPs and resulting sensing performances, thereby providing guidelines for e-MIPs synthesis. As a proof-of-concept, cortisol (template)–pyrrole (monomer) system is selected in this research due to the following reasons: (1) cortisol, popularly called “stress hormone”, is a highly valuable biomarker to be measured for stress management and personalized health monitoring, (2) pyrrole is a widely used monomer for electropolymerization, and computational studies show that pyrrole can form more specific and stronger interaction with cortisol than other interfering steroid hormones (e.g., progesterone, prednisolone), (3) overoxidation of imprinted polypyrrole (PPy) can be used to extract cortisol from the polymer matrix, , which is more controllable and repeatable than other chemical removal methods. While there are various surrogate models available for elucidating the causative relation of input and output in the experimental data set, in this research, we used the Gaussian process (GP) because it is intrinsically probabilistic that it is capable of accounting for the effects of inevitable measurement variations and synthesis uncertainties when performing model training and prediction. , This tightly aligns with the stochastic nature of real-world problems.…”
Section: Introductionmentioning
confidence: 99%
“…The mainstay of this framework is a surrogate model, upon which tailored data analytics methods can be further employed to quantify the relationship between synthesis parameters of e-MIPs and resulting sensing performances, thereby providing guidelines for e-MIPs synthesis. As a proof-of-concept, cortisol (template)–pyrrole (monomer) system is selected in this research due to the following reasons: (1) cortisol, popularly called “stress hormone”, is a highly valuable biomarker to be measured for stress management and personalized health monitoring, (2) pyrrole is a widely used monomer for electropolymerization, and computational studies show that pyrrole can form more specific and stronger interaction with cortisol than other interfering steroid hormones (e.g., progesterone, prednisolone), (3) overoxidation of imprinted polypyrrole (PPy) can be used to extract cortisol from the polymer matrix, , which is more controllable and repeatable than other chemical removal methods. While there are various surrogate models available for elucidating the causative relation of input and output in the experimental data set, in this research, we used the Gaussian process (GP) because it is intrinsically probabilistic that it is capable of accounting for the effects of inevitable measurement variations and synthesis uncertainties when performing model training and prediction. , This tightly aligns with the stochastic nature of real-world problems.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, electrochemical polymerization techniques offer a simple, one-step process of directly depositing an MIP on the electrode surface with a greater degree of control over polymer morphology . Computational studies have suggested that pyrrole-based polymers are suitable for fabricating cortisol-specific electrochemical MIP sensors. , The oxygen-containing electronegative functional groups present on the cortisol can interact with electropositive hydrogen attached to the nitrogen of pyrrole via hydrogen bonding, which helps in encapsulating cortisol in the polypyrrole (PPy) network during electropolymerization. Pyrrole can be electrochemically polymerized under ambient conditions, and the resulting PPy is stable and conductive in neutral pH, making it an excellent candidate for physiological MIPs and other sensing applications. , …”
Section: Introductionmentioning
confidence: 99%
“…Reasonable correlations were found among the predicted IR, Raman and UV spectra with the corresponding experimental ones [56]. The calculations of gap values [54] and some descriptors were performed, as suggested by Parr and Pearson [59][60][61][62][63][64][65][66][67][68], because the prediction of reactivities and behaviours in the three media are of interest for this hormone with anti-inflammatory and immunosuppressive properties [20,21,23,27,[30][31][32][35][36][37][39][40][41][42][43][44].…”
Section: Methodsmentioning
confidence: 99%
“…The IUPAC name of corticosterone is (11β)-11,21-dihydroxypregn-4-ene-3,20-dione although it is also known as 11β,21-dihydroxyprogesterone or simply as 17-deoxycortisol . The adrenal gland produces this hormone with antiinflammatory and immunosuppressive properties [20,21,23,27,[30][31][32][35][36][37][39][40][41][42][43][44]. So far, there are a lot of articles related to structural, chemical and biological studies on glucocorticoids, from experimental studies by using spectroscopic and electrochemical techniques up to different theoretical studies because these species present dual regulation effects on the immune function which are strongly dependent on the concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation